Papers Relating to the Formulation of the Second Five Year Plan - Planning Commission, government of India (Planning Commission, government of India, 1955)
An attempt has been made in this paper to work out the targets to be achieved in the Second Plan period in the light of the main objectives in view. The purpose is to present a rough sketch of the overall picture or pattern which the Second Plan should aim at. The detailed targets to be achieved will, of course, have to be arrived at only after a detailed scrutiny of needs and of the means and measures required for their fulfillment. A broad framework is, however, necessary if individual schemes and targets are to be worked out by the authorities concerned with an eye to the overall developments envisaged.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Memorandum of the Panel of Economists and Note of Dissent by Prof. B.R. Shenoy; The Plan Frame; Capital Formation and Investment Pattern